An optimal innovation based adaptive estimation Kalman filter for accurate positioning in a vehicular ad-hoc network - Vadivel, Ramanathan; Sumithra, S. (Zielona Góra: Uniwersytet Zielonogórski)
The vehicular ad-hoc network (VANET) is subject to various attacks because of its dynamic nature and ephemeral character. In VANET, vehicles communicate with each other for safety awareness. The positioning of an unknown vehicle is one of the critical factors to determine the vehicle?s trustworthiness. Although some positioning techniques have achieved a high accuracy level in VANET, they suffer from dynamic noise in real-world environments. This drawback leads to inaccuracy and unreliability during vehicle positioning.
Keywords: Kalman filters; innovation; dead reckoning (DR); global positioning system (GPS); simulation of urban mobility (SUMO)